Analysis of Macroeconomic Variables on Demand for Money in Indonesia - Veisa Arthamevia Alif; Mahrus Lutfi Adi Kurniawan (INCOME: Innovation of Economics and Management, 2024)
This research aims to determine the influence of macroeconomic variables on the demand for money in Indonesia. The research applies the broad money variable (M2) as the dependent variable, this includes M1, quasi money (including savings, time deposits in rupiah and foreign currency, as well as current accounts in foreign currency), and securities issued by the monetary system owned by the domestic private sector with a remaining term of up to one year. The research uses time-series data from 1993-2023 and the OLS method. The research results show that exports influence the demand for money, a positive coefficient value indicates that increasing exports will increase the money supply. The GDP variable has a negative effect on the money supply in Indonesia, the higher the GDP, the money supply will decrease which can be caused by a decrease in people's purchasing power, the transfer of "wealth" to other instruments and the role of money which is used more as savings by the public. Depreciation of the exchange rate causes the prices of imported goods to become more expensive. Apart from that, it can affect the condition of the domestic economy which causes a decrease in people's purchasing power so that it can reduce the money supply and inflation has no effect on the money supply in Indonesia. The implication of the research is that government policies are needed that encourage people's purchasing power and exchange rate stability to improve the domestic economy